Mechanism of 5-fluorouracil required resistance in human hepatocellular carcinoma cell line Bel(7402) - Jin, Jing (World J Gastroenterol, 2002)
AIM: To investigate the resistance mechanism of 5-fluorouracil (5-FU) in Bel(7402)/5-FU cells which was established in our lab by in vitro continuous stepwise exposure of human hepatocellular carcinoma (HCC) cell line Bel(7402) to 5-FU. METHODS: The expression of multidrug resistance-associated protein (MRP) and thymidylate synthase (TS) in Bel(7402) cells was detected by immonocytochemistry. The fluorescein (FLU) accumulation, an index of MRP functional activity, was determined by flow cytometry. The distribution of FLU was observed by confocal laser scanning microscope. The spectrofluorometry was used to show the intracelluar content of glutathione (GSH). Cell growth inhibition was determined by MTT assay. The activity of glutathione S-transferases (GSTs) was determined by spectrophotometry. RESULTS: A higher expression of MRP in the Bel(7402)/5-FU cells was observed by using monoclonal mouse anti-MRP antibody, MRPr-1, in comparison with Bel(7402) cells. Bel(7402)/5-FU cells also showed a significant decrease of FLU accumulation. FLU mainly accumulated in the nucleus with a high nuclear/cytoplasmic ratio in Bel(7402) cells, whereas there was no difference of FLU accumulation between the nucleus and cytoplasm in Bel(7402)/5-FU cells. The intracellular GSH content in Bel(7402)/5-FU cells was almost 3 folds higher than that in Bel(7402) cells. Addition of D, L-buthione-S, R-sulfoximine (BSO) dose-dependently reduced the GSH content in Bel(7402)/ 5-FU cells, however, only a weak enhancement on the cytotoxicity of 5-FU and doxorubicin (Dox) to Bel(7402)/5-FU cells was observed. Bel(7402)/5-FU cells also exhibited 29.1% higher total GSTs activity than Bel(7402) cells. Immunocytochemical staining by using anti-TS monoclonal antibody TS 106 showed that the level of TS in Bel(7402)/5-FU cells elevated markedly as compared with Bel(7402) cells. CONCLUSION: The continuous exposure of Bel(7402) cells to 5-FU led to overexpression of TS and MRP, as well as increased intracellular GSH content and total GST activity.